Supernatural. Season ten [videorecording (DVD)] - Padalecki, Jared, 1982-; Ackles, Jensen; Collins, Misha; Sheppard, Mark, 1964-; Beaver, Jim, 1950-; Calvert, Alexander; Smith, Samantha, 1969-; Pellegrino, Mark (Warner Home Video, 2021)
Sam and Dean spend their lives on the road, battling every kind of otherworldly threat. Over the years, in dozens of bloody adventures, they face everything from the yellow-eyed demon that killed their mother to vampires, ghosts, shape-shifters, angels, fallen gods, and even Lucifer and God themselves.